Tritodynamia serratipes sp. nov., a new marine crab from Singapore (Crustacea: Decapoda: Brachyura: Macrophthalmidae) - Anker, Arthur; Ng, Peter K. L. (Zootaxa, 2014)
Tritodynamia serratipes sp. nov. is described based on a female specimen dredged on soft mud at a depth of 6.3–6.5 m, near Marina East, only a few kilometers from Singapore’s city centre. The new species differs from all other species of Tritodynamia Ortmann, 1894 by a unique combination of morphological characters, including the posterior margin of the propodus of the second ambulatory leg armed with a row of particularly strong teeth, and the cutting edges of dactylus and pollex each proximally armed with two stout teeth. Tritodynamia serratipes sp. nov. is the second species of the genus described from tropical Asia.